Analisis Sistem Pengupahan Terhadap Karyawan Dalam Perspektif Ekonomi Islam Di PT. Tania Selatan Kebun Burnai Timur Kab. Ogan Komering Ilir - Tri Kurnia Larasati; Hilda; Syamsiar Zahrani (CV. ITTC INDONESIA, 2022)
Indonesia is one of the countries with the largest Muslim majority population in the world. That is 87.2% of the total population in Indonesia. With that, the Indonesian people are no stranger to Islamic Economics. However, in reality, in the field there are many wage system practices that are inappropriate or not in accordance with Islamic Economics. This study aims to find out how the wage system for fertilizer employees at PT. South Tania East Burnai Gardens and find out how the wage system for fertilizing employees at PT. South Tania East Burnai Gardens in the Perspective of Islamic Economics. The research method used in this study is a qualitative descriptive method, data collection techniques using interviews, and documentation..Based on data obtained in the field, there were 11 samples studied, consisting of 1 Division 1 Field Offiver and 10 fertilizing employees at PT. South Tania East Burnai Gardens, Ogan Komering Ilir Regency, researchers received information that the method of remuneration carried out at PT. Tania Selatan Kebun Burnai Timur is given once a month not later than the 7th. The wages given are also in accordance with the UMR (Regional Minimum Wage). Before doing work, employees are notified in advance of the amount of wages received so that nothing becomes a benchmark in giving their wages. If there is an increase in wages, the employee will also be notified by the company. The results showed that the Islamic Economics wage system PT. South Tania East Burnai Gardens have not been fully said to be good, because not all values in Islam have been implemented, namely justice and fairness. The wage system applied at PT. Tania Selatan East Burnai Plantation can be said to be fair, because the workers there get paid according to the work they have done and there is no difference in wages with other fertilizer employees. Islamic Economic wage system PT. South Tania East Burnai Plantation can be said to be feasible, because the wages are in accordance with the UMR in the area. Employee wages are also in accordance with the work that employees do. While decent in the sense that it can meet the needs of clothing, food, housing for employees and their families, the wages given by the company cannot be said to be proper. Because employees feel that the wages they receive cannot meet the needs of them and their families.